Falls in the stationary for patients with cardiovascular diseases of the senior age and polypharmacy - E. S. Ilina; O. T. Bogova; I. I. Sinitsina; S. N. Puzin; D. A. Sychev (Нервно-мышечные болезни, 2018)
Background. The fall in the elderly is observed much more often than in younger people, and according to statistics the number of people over 65 years who have suffered a fall during the year reaches 30 %, while the probability of injury. Most of the falls in elderly patients does not lead to injury, but the developing at the same time unfavorable psychological discomfort can sharply limit the usual activity, lead to the formation of dependence on outside help, disadaptation in the home and form a fear of a possible fall. Falls, accompanied by the development of trauma, are observed in 10–15 % of cases. The objective was to study the relationship between polymorbidity, polypragmasia and the development of the fall in elderly patients cardiological profile.Results. Polymorbidity prevailed in the group of patients who suffered a fall in the hospital (8.9 ± 2.6 vs 7.5 ± 1.5 in men. 8.5 ± 2.2 vs 7.2 ± 1.6 in women). In patients undergoing a decline, it was also noted, and polypharmacy to a greater extent than cohort patients without falling (9.4 ± 1.9 vs 78.4 ± 2.2 in men. and 9.6 ± 2.7 vs 9.1 ± 2.5 for women). In addition, patients who suffered a fall in the hospital by age were older than patients in the comparison group (86 ± 6 vs 85 ± 5 in men, 87 ± 5 vs 84 ± 5 in women). We also revealed the tendency of the predominance of women in the subgroup of patients with the incidence and development of trauma. Conclusion. Minimizing the amount of drugs received, as the fight against polypragmasy can help reduce the incidence of falls in elderly patients.